An analytical approach for modelling the vibroacoustic behaviour of a heavy fluid-loaded plate near a free surface. (10th November 2022) - Kha, Jamie; Karimi, Mahmoud; Maxit, Laurent; Skvortsov, Alex; Kirby, Ray
Abstract: Predictions of the vibroacoustic response of a point-force excited baffled thin rectangular plate immersed in a heavy fluid and near a free surface are presented using an analytical model. The equations of motion are solved by Fourier analysis, where the eigenfunctions of plate vibration form the basis of spatial expansion for fluid loading. Vibroacoustic indicators, including the plate velocity, acoustic pressure, and acoustic power, are predicted using the analytical approach and verification is performed by comparison with finite element simulations. The results have shown that variations in the height of the free surface can have a significant effect on these indicators. From the vibration response, added mass effect due to heavy fluid loading is altered and further investigated with the explicit evaluation of an added mass ratio for different free surface heights for the first five plate modes. For a given height of a free surface, standing waves can form between the free surface and baffled plate at specific excitation frequencies and slightly alters the acoustic pressure spectra. This condition also presents an effect on the acoustic power, where the first standing wave frequency dictates the efficient sound radiation to the far field. Highlights: Vibroacoustics of a heavy fluid-loaded plate near a free surface is examined. An analytical model is developed to provide efficient parametric studies. Effect of standing waves on the radiated acoustic pressure is studied. The presence of a free surface significantly affects the radiated acoustic power.